The research of the ultrastructural and morphofunctional peculiarities of a muscular system of the Prosthogonimus cuneatus trematode (Experimental biology, 2016)
The issue on the structural and functional organization of a muscular system of trematodes is considered in the article. We give a complete characterization and analysis of the functional morphology of the features of the muscular system fluke Prosthogonimus cuneatus. The analysis of materials of preceding researches, articles of foreign authors, as well as of additional literature, reflecting peculiarities of structure of a body musculature of trematodes, is accomplished. The characteristic peculiarities of trematodes’ body musculature, separate organs and systems are singled out and described. The article is devoted to the detailed analysis of trematodes’ organs of localization. Particular attention is paid to the analysis of longitudinal body musculature and dorsoventral muscles.
Keywords: ultrastructure; muscular apparatus of trematodes; mitochondria; sarcolemma; Prosthogonimus; tegument; bursa of Fabricius; localization organ.